Analysis of The Effect of Growth Domestic Product Growth, Consumer Price Index, Inflation, BI Interst Rate, and The Rupiah-Dollar Exchange Rate on Gold Price - Septevenus, William; Lesmana , Iwan; Sitardja , Meco; Biantara, Dheny; Handayani, Sri (Journal of Economics and Business (JECOMBI), 2025)
This research aims to analyze macroeconomics factors that affect the Gold Price. The variables in this study are Gross Domestic Product Growth, Consumer Price Index, Inflation, BI Rate, Exchange Rate. The sample used in this research is secondary data of Gold Price in investing.com on the period from 2005-2020. Using SPSS (statistical package for the social science), methods of analysis used in this study include tolerance and VIF test, Kolmogorov- Smirnov test, multivariate cointegration tests: Test, SRESID and ZPRED estimation, t-statistical tests, F- statistical test, coefficient of determination (R2), and Pearson Correlation Product Moment. The result of this research shows Gross Domestic Product Growth, BI Rate, Exchange Rate have significant influence on the Gold Price, but Consumer Price Index and inflation have no significant influence on the Gold Price. All the independent variables simultaneously from a good model to explain the Gold Price since the magnitude of the effect value is 90,1% while 9,9% is explained by other variables besides Gross Domestic Product Growth, Consumer Price Index, Inflation, BI Rate, Exchange Rate. The formula that was found from this research could be used as a tool in predicting Gold Price. Keywords: Gold Price, Gross Domestic Product Growth, Consumer Price Index, Inflation, BI Rate, Exchange Rate.